2005
DOI: 10.1104/pp.105.065110
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Families Have Much Higher Expansion Rates in Plants than in Animals

Abstract: (M.-C.S.) Transcription factors (TFs), which are central to the regulation of gene expression, are usually members of multigene families. In plants, they are involved in diverse processes such as developmental control and elicitation of defense and stress responses. To investigate if differences exist in the expansion patterns of TF gene families between plants and other eukaryotes, we first used Arabidopsis (Arabidopsis thaliana) TFs to identify TF DNA-binding domains. These DNA-binding domains were then u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
163
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(175 citation statements)
references
References 64 publications
10
163
0
2
Order By: Relevance
“…They estimate that these whole-genome duplication events are responsible for about 90% of the transcription factor in higher plants. Indeed, the rate of transcription factor evolution is thought to be higher in plants than in animals (Shiu et al, 2005). This contrasts with proteins involved in secondary metabolism or abiotic stress, where those derived by small segmental duplications tended to be retained, whereas those derived by whole-genome duplications were more rapidly lost (Maere et al, 2005).…”
Section: Analyses Of Expressed Sequence Tags From Applementioning
confidence: 43%
“…They estimate that these whole-genome duplication events are responsible for about 90% of the transcription factor in higher plants. Indeed, the rate of transcription factor evolution is thought to be higher in plants than in animals (Shiu et al, 2005). This contrasts with proteins involved in secondary metabolism or abiotic stress, where those derived by small segmental duplications tended to be retained, whereas those derived by whole-genome duplications were more rapidly lost (Maere et al, 2005).…”
Section: Analyses Of Expressed Sequence Tags From Applementioning
confidence: 43%
“…Most tandem arrays contain only two duplicated genes, and arrays with more than three members are rare (Rizzon et al, 2006). Although transcription factor families have much higher expansion rates in plants than in animals (Shiu et al, 2005), the Arabidopsis genome contains only one region with more than five duplicated transcription factor genes in tandem, whereas several such regions are present in soybean (Glycine max; Schmutz et al, 2010). Apparently, the clustering of more than seven duplicated transcription factor genes at the NIC2 locus is a rare event in the evolution of tobacco.…”
Section: Discussion the Nic2 Locus Comprises At Least Seven Clusteredmentioning
confidence: 99%
“…These studies have also shown that evolutionarily younger genes tend to be expressed at earlier and later stages of development, whereas the transcriptomes of the middle stages (the phylotypic stage) are dominated by ancient genes (10, 13). It remains to be investigated how the evolutionary age and the expression patterns of the different TFs shift throughout the ontogeny of these lineages and whether TF expression profiles correlate with the general transcriptome profiles.Previous studies have analyzed the evolutionary history and phylogenetic distribution of TFs in various branches of the tree of life (6,(15)(16)(17)(18)(19)(20)(21)(22). However, it is not yet clear whether the evolutionary scenarios previously proposed are robust to the incorporation of genome data from key phylogenetic taxa that were previously unavailable.…”
mentioning
confidence: 99%